Disentangling topographic and climatic controls on glacier length: A case study in the tropical Colombian Andes - Joel A. Wilner; Alice M. Doughty; Meredith A. Kelly; Mathieu Morlighem (Earth and Planetary Science Letters, 2025)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Emerging and re-emerging infectious diseases in pregnant women in an amazonian region: a large retrospective study from French Guiana - Najeh Hcini; Véronique Lambert; Jean-François Carod; Meredith Mathieu; Gabriel Carles; Olivier Picone; Jeanne Sibiude; Leo Pomar; Mathieu Nacher (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Scaled mass index derived from aerial photogrammetry associated with predicted metabolic pathway disruptions in free-ranging St. Lawrence Estuary belugas - Meredith Sherrill; Alexandre Bernier-Graveline; Jessica Ewald; Zhiqiang Pang; Michel Moisan; Mathieu Marzelière; Maris Muzzy; Tracy A. Romano; Robert Michaud; Jonathan Verreault (Frontiers in Marine Science, 2024)
The St. Lawrence Estuary (SLE) belugas (Quebec, Canada) are an endangered population whose numbers remain low despite ongoing conservation efforts. Multiple anthropogenic factors and changing environmental conditions are thought to have contributed to the recent 20-year decline in blubber fatty acid concentrations reported in stranded SLE belugas. Despite this evidence that energy reserves within the population are declining, there is currently no method for estimating the body condition of free-ranging animals. The potential metabolic consequences of declining fat reserves have also yet to be explored. The objectives of this study were to use unmanned aerial vehicle (UAV)-based photogrammetry to estimate the scaled mass index (SMI) of free-ranging SLE belugas, and to compare this proxy of body condition to the lipidome of outer-layer blubber samples collected from the same individuals via remote biopsy darting. Morphometric analysis of aerial images ( n = 44 SLE belugas), combined with data collected from animals under professional human care, produced SMI estimates (females: 807 ± 98 kg, males: 743 ± 39 kg) similar in range to those previously calculated for SLE beluga carcasses of known weight. A non-targeted lipidomic analysis followed by pathway enrichment analysis, identified metabolic pathways predicted to show altered activity in association with SMI in the blubber of free-ranging male SLE belugas ( n = 27). Mapping of enriched pathways compared to the Kyoto Encyclopedia of Genes and Genomes (KEGG) metabolic pathways maps, revealed that enriched pathways pertained to the metabolism of multiple lipid classes including fatty acyls and glycerophospholipids. Vitamin A, Vitamin E, and tyrosine metabolism pathways were also enriched in correlation with SMI. This study provides the basis for the development of a non-invasive technique for estimating the body condition of free-ranging SLE belugas and identifies metabolic pathways that merit further exploration to improve our understanding of the potential metabolic impacts of energy loss in cetaceans.